Republic of Yemen : Unlocking the Potential for Economic Growth - World Bank (World Bank, Washington, DC, 2016)
Part one of the report provides an overview of the economy. It has one chapter (chapter one), which provides an overview of the country’s growth and macroeconomic performance and challenges and analyzes and emphasizes the limited dynamism of a rent- and hydrocarbon-cursed economy. Part II describes cross-cutting issues that constrain policy implementation, regardless of the sectors where they occur. In chapter two, the report draws on material outlined in the rest of the report to argue that the policy problems that undermine the country’s development can be linked directly to political distortions introduced by the fragmentation among the population and the elites. While the informal elite networks are able to block reform and aggressively continue to seek rents that might otherwise be recycled into development, the population is unable to exert its rights and hold the elites accountable. Chapter three analyzes the major impediments in the business environment. Through the analysis of the de jure legal and regulatory business environment as well as the enforcement of business regulations, the chapter identifies key legal and institutional changes that can help reduce the opportunities for rent seeking that favor well-connected businesses. Chapter four discusses the opportunities to maximize the benefits of the country’s human capital by enhancing the quality of worker skills, increasing women’s labor force participation, and facilitating the migration of Yemenis to work in the Gulf Cooperation Council (GCC) countries. To achieve this goal, the Republic of Yemen needs to enhance the quality of the education system, especially technical education and vocational training (TEVT), and respond to the existing demand for skilled workers. Chapter five explores the constraints to realizing the potential of agriculture. It argues that a key constraint on the sector is the capture of land and water by multiple elites motivated by short-term rent extraction, which prevents the efficient management of these assets and therefore undermines any possibility of sustainable development. The chapter also discusses other constraints and weaknesses affecting the sector and proposes legal and institutional changes that could help increase transparency in the management of the sector. Chapter six analyzes the prospects for growth in the oil and gas sector and discusses key governance reforms that would help reduce rent seeking in the sector.